2023
DOI: 10.1007/s00204-023-03482-8
|View full text |Cite
|
Sign up to set email alerts
|

Potency ranking of pyrrolizidine alkaloids in metabolically competent human liver cancer cells and primary human hepatocytes using a genotoxicity test battery

Abstract: Pyrrolizidine alkaloids (PAs) occur as contaminants in plant-based foods and herbal medicines. Following metabolic activation by cytochrome P450 (CYP) enzymes, PAs induce DNA damage, hepatotoxicity and can cause liver cancer in rodents. There is ample evidence that the chemical structure of PAs determines their toxicity. However, more quantitative genotoxicity data are required, particularly in primary human hepatocytes (PHH). Here, the genotoxicity of eleven structurally different PAs was investigated in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…In the present work, we investigated the relevance of OCT1 for the uptake of structurally diverse PAs in metabolically competent human HepG2-CYP3A4 cells, Chinese hamster V79-CYP3A4 cells and PHH. HepG2-CYP3A4 cells were revealed as a very useful model in our previous study, since the genotoxic and cytotoxic potency of structurally diverse PAs was in very good agreement with that obtained in PHH as gold standard (Haas et al 2023 ). Furthermore, HepG2 cells were reported to display OCT1 gene expression, although the expression levels were lower than those in PHH (Herzog et al 2016 ; Rodrigues et al 2009 ).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In the present work, we investigated the relevance of OCT1 for the uptake of structurally diverse PAs in metabolically competent human HepG2-CYP3A4 cells, Chinese hamster V79-CYP3A4 cells and PHH. HepG2-CYP3A4 cells were revealed as a very useful model in our previous study, since the genotoxic and cytotoxic potency of structurally diverse PAs was in very good agreement with that obtained in PHH as gold standard (Haas et al 2023 ). Furthermore, HepG2 cells were reported to display OCT1 gene expression, although the expression levels were lower than those in PHH (Herzog et al 2016 ; Rodrigues et al 2009 ).…”
Section: Discussionsupporting
confidence: 72%
“…This biotransformation step gives rise to dehydro-pyrrolizidine derivatives (dehydro-PAs) and, upon hydrolysis, to (±)-6,7-dihydro-7-hydroxy-1-hydroxymethyl-5H-pyrrolizine (DHP), which both react with DNA and proteins (Edgar 2014 ; Fu 2017 ). A plethora of studies performed in different liver cell models including human primary hepatocytes demonstrated a structure–toxicity relationship for PAs, supporting the concept of grouping PAs into potency classes (Allemang et al 2018 ; Gao et al 2020 ; Haas et al 2023 ; Hadi et al 2021 ; Lester et al 2019 ; Louisse et al 2019 ; Merz and Schrenk 2016 ; Rutz et al 2020 ).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations